Role of women in Indian independence movement: भारतीय स्वाधीनता आंदोलन में महिलाओं की भूमिका - Meena, Ramjeelal (RESEARCH HUB International Multidisciplinary Research Journal, 2023)
During British rule in India, the British repeatedly claimed their aim was to establish a prosperous, welfare-driven state and modernize the nation by eradicating social issues. However, their true objective was to exploit India’s economy to strengthen their capitalist system. Amid this era, social reformers, influenced by British education and Western ideas, focused on women’s conditions. Noteworthy figures like Raja Rammohan Roy, Dayanand Saraswati, Ishwarchand Vidyasagar, Ramakrishna Paramhans, Keshavchandra, and Mahadev Govind Ranade sought women’s emancipation. As many reformers were upper-caste, they targeted oppression of elite women. Mahadev Govind Ranade stated that the 19th-century reform movement aligned with Hindu tradition. They highlighted that ancient India lacked practices like Sati and emphasized the high regard for women in pre-Buddhist Hindu theology and law. Raja Ram Mohan Roy and others used ancient scriptures to challenge customs like Sati. Abstract in Hindi Language: भारत में ब्रिटिश शासन के दौरान, अंग्रेज बार-बार दावा करते थे कि उनका उद्देश्य एक समृद्ध, कल्याण-संचालित राज्य की स्थापना करना और सामाजिक मुद्दों को खत्म करके राष्ट्र का आधुनिकीकरण करना है। हालाँकि, उनका असली उद्देश्य अपनी पूंजीवादी व्यवस्था को मजबूत करने के लिए भारत की अर्थव्यवस्था का शोषण करना था। इस युग के दौरान, ब्रिटिश शिक्षा और पश्चिमी विचारों से प्रभावित समाज सुधारकों ने महिलाओं की स्थिति पर ध्यान केंद्रित किया। राजा राममोहन राय, दयानंद सरस्वती, ईश्वरचंद विद्यासागर, रामकृष्ण परमहंस, केशवचंद्र और महादेव गोविंद रानाडे जैसी उल्लेखनीय हस्तियों ने महिलाओं की मुक्ति की मांग की। चूंकि कई सुधारक ऊंची जाति के थे, इसलिए उन्होंने कुलीन महिलाओं पर अत्याचार को निशाना बनाया। महादेव गोविंद रानाडे ने कहा कि 19वीं सदी का सुधार आंदोलन हिंदू परंपरा के अनुरूप था। उन्होंने इस बात पर प्रकाश डाला कि प्राचीन भारत में सती जैसी प्रथाओं का अभाव था और बौद्ध पूर्व हिंदू धर्मशास्त्र और कानून में महिलाओं के लिए उच्च सम्मान पर जोर दिया गया। राजा राम मोहन राय और अन्य लोगों ने सती जैसी प्रथाओं को चुनौती देने के लिए प्राचीन ग्रंथों का इस्तेमाल किया। Keywords: पूंजीवादी व्यवस्था, समाज सुधारक, दयानंद सरस्वती, आंदोलन